Pengaruh Penyuluhan Kesehatan Gigi dan Mulut Menggunakan Flip- chart Terhadap Tingkat Pengetahuan Menyikat Gigi Bagi Siswa Sekolah Dasar Remaja Parakan - Pratiwi, Eka; Haryani, Wiworo; Purwati, Dwi Eni (Journal of Oral Health Care, 2019)
Dental and oral health care is carried out from an early age. Lack of knowledge level of students in brushing teeth makes teeth easily damaged. A flipchart needed for counselling to increase knowledge in brushing teeth for elementary students. Objectives: To find out the influence dental and oral health education using flipchart for students at primary school Remaja Parakan based on their knowledge level at teeth brushing The design of this study was quasi-experimental with a non- randomized control group pretest posttest design. The number of respondents was 80 students. The sample was divided into 40 respondents in the experimental group and 40 respondents in the control group. The data is obtained through a questionnaire. Data analysis using the Wilcox- on Signed Rank Test to find out repeated tests on two conditions and Mann Whitney Test to find out differences between two group. The knowledge level of the pretest experimental group was 90% in the wrong category. After the intervention, the knowledge level of the post-test increased to 85% in the first category. The knowledge level of the pretest of the control group was 55% in the medium grade,after intervention the knowledge level of the post-test increased to 5% in the excellent category and 95% in the medium category, with pretest and posttest analysis using the Wilcoxon Signed Rank Test showing both groups had significant differences with a value of p = 0.00 (p <0.05). Mann Whitney analysis shows the mean rank of the experimental group > control group, which is 59.03> 21.98. The knowledge level of teeth brushing after being given ed- ucation with flipchart media in elementary school students is increasing